Integration Of The Enterprise Information To Facilitate Decision Making - Hilario, Manuel; Esenarro, Doris; Vega, Hugo; Rodriguez, Ciro (The journal of contemporary issues in business and government, 2021)
The research objective is to apply business intelligence techniques to take advantage of an existing system's conditions and increase the low-cost capabilities in its Extract, Transform and Load ETL processes with snapshots integrating the company's information web services. The methodology used for the development was HEFESTO, the development time was one week applying agile methodologies, achieving a short development with well- defined and easy-to-understand phases; the tool was the Pentaho BI Suite. Using open source tools, the cost was reduced through the proposed architecture with the repository type and the DataMart with a departmental approach to the problem, increasing its decision-making capacity.